2009
DOI: 10.1111/j.1467-9906.2009.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Mismatch of the Poor: An Explanation of Recent Declines in Job Isolation

Abstract: Despite years of spatial mismatch hypothesis research, the poor's access to jobs is not well understood. This article provides a detailed analysis of the distributional imbalance between the residential locations of poor and nonpoor families and jobs over the 1990s in U.S. metropolitan areas. Descriptive and multivariate evidence are presented addressing whether job access for the poor has improved over the 1990s. If so, what factors drove the improvement, and do they help explain the disparity in job access b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…There is a countervailing relationship wherein job sprawl performs as a push factor in low-income neighborhoods and as expected may perform as a pull factor in highincome suburbs (this finding is only significant in the unweighted result). This finding supports the literature; various scholars have shown that the poor in particular follow jobs to shrink distance to job rich clusters on the urban fringe (see Covington (2009) Clearly, affordable housing opens up access to neighborhoods, and lack thereof, render suburban migration by the poor a less likely process. Despite the best efforts, there are strong views against affordable housing.…”
Section: Discussionsupporting
confidence: 80%
“…There is a countervailing relationship wherein job sprawl performs as a push factor in low-income neighborhoods and as expected may perform as a pull factor in highincome suburbs (this finding is only significant in the unweighted result). This finding supports the literature; various scholars have shown that the poor in particular follow jobs to shrink distance to job rich clusters on the urban fringe (see Covington (2009) Clearly, affordable housing opens up access to neighborhoods, and lack thereof, render suburban migration by the poor a less likely process. Despite the best efforts, there are strong views against affordable housing.…”
Section: Discussionsupporting
confidence: 80%
“…2 Recent research has attempted to measure spatial mismatch conditions uniformly across U.S. metropolitan areas using indices of dissimilarity between people and jobs, or a variant thereof. This research indicates large and statistically significant racial/ethnic differences in geographic imbalances of people and jobs remain through the 2000 period (Covington, 2009;Raphael and Stoll, 2002;Martin, 2004). 3 Over the 1990s, racial segregation between blacks and others, in particular whites, fell as it had over the previous decade (Glaeser and Vigdor, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Of course, spatial mismatch refers to the geographic separation of groups from jobs, and previous empirical research has demonstrated that blacks', and to a lesser extent Latinos' geographic job access is inferior to that of whites (Covington, 2009;Johnson, 2006;Raphael and Stoll, 2002). 1 1 Of course, the largest body of work in this area examines whether and how distance from jobs harms labor market outcomes, and whether blacks' inferior outcomes are related to their greater degrees of spatial mismatch (Ihlanfeldt and Sjoquist, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Liu and Painter (2012) fi nd similar changes for immigrants in 60 metropolitan areas between 1980 and 2000. Covington (2009) also observes narrower gaps between the poor and the non-poor in 2000 than in 1990, particularly for Black poor. All three studies, however, also use the dissimilarity index, which overlooks intra-metropolitan spatial disparities.…”
Section: Suburbanization and Spatial Mismatchmentioning
confidence: 79%